Organization of the epidemiological surveillance on nonpolioenterovirus infection among children in Azerbaijan in modern stage - L. I. Rustamova (Детские инфекции (Москва))
The aim of investigation is to analyses of some prerequisites for improving of organization of the epidemiological surveillance on nonpolioenterovirus infection among children in Azerbaijan in modern stage.For this purpose the statistic datas about morbidity with «intestinal infection of uncertain etiology» and «nonpolioenterovirus ifection» among children have been and lysed and presented.The results of conducted retrospective and prospective epidemiological analyses aloow to determine the main key steps for improving of the epidemiological surveillance on nonpolioenterovirus infection among children in Aherbaijan, which are the followig: the dynamic of intrayearly and manyyearly morbidity of nonpolioenterovirus infection; the serotypical spectrum and the virulency of nonpolioenteroviruses; the virological control of surface and waste waters for appearing of nonpolioenteroviruses; the regular monitoring of «healthy» viruscarrier among children contingents (organized and nonorganized).